Pyrolusite: An alternative oxygen carrier for chemical looping combustion. (1st December 2016) - Perreault, Patrice; Rifflart, Sébastien; Nguyen, Elizabeth; Patience, Gregory-S.
Highlights: 16 minerals were tested as alternative to synthetic nickel oxide and ilmenite. Pyrolusite, a manganese oxide mineral, can transfer up to 3 times oxygen compared to ilmenite. Oxygen transfer capacity is doubled when calcined under high oxygen partial pressure and reduced under methane. Pyrolusite has adequate attrition resistance and costs fraction of ilmenite. Abstract: Identifying an economic alternative to nickel oxide that is non-toxic, and stable over thousands of cycles continues to drive chemical-looping process development. Mineral ores meet many of these criteria and ilmenite is prominent among the ores tested to date. However, pyrolusite, a manganese oxide containing more than 85% amorphous MnO2 in its fresh form, can transfer more than 3 times oxygen compared to ilmenite — as much as 7% of its own mass. In addition, the oxygen transfer capacity can be increased by preheating pyrolusite under an oxidizing atmosphere. It can then transfer almost double its experimental oxygen transfer capacity versus pyrolusite pre-treated in an inert environment. Together with excellent oxygen carrying capacity, it has adequate attrition resistance and costs fraction of ilmenite. In addition, the solid inventory in the reduction reactor would represent 8% of that required for ilmenite and the solid circulation would drop by 30%, but the fresh particle makeup would be 4 times higher based on measurements from a laboratory-scale submerged jet attrition mill.